2006
DOI: 10.1111/j.1445-2197.2006.03723.x
|View full text |Cite
|
Sign up to set email alerts
|

Children or Young Adults? A Population‐based Study on Adolescent Head Injury

Abstract: The study emphasizes the incidence of and mortality from adolescent head injury. The pattern of adolescent head injury is different from that of children and supports current practice of treatment of a majority of adolescents in adult trauma centres. These differences have implications on planning for injury prevention and trauma management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
10
0
2
Order By: Relevance
“…Some studies have identified the same incidence peeks in teenagers and young adults (Kraus and Arthur, 1996). A retrospective study in the State of Victoria revealed that motor vehicle drivers and passengers accounted for 40% of all significant head injuries in adolescents and 45% in young adults (Mitra et al, 2006). These study findings show that the people of the most active and productive age group are involved in road traffic crashes and sustain head injuries and which has a serious economic impact on the community.…”
Section: Discussionmentioning
confidence: 92%
“…Some studies have identified the same incidence peeks in teenagers and young adults (Kraus and Arthur, 1996). A retrospective study in the State of Victoria revealed that motor vehicle drivers and passengers accounted for 40% of all significant head injuries in adolescents and 45% in young adults (Mitra et al, 2006). These study findings show that the people of the most active and productive age group are involved in road traffic crashes and sustain head injuries and which has a serious economic impact on the community.…”
Section: Discussionmentioning
confidence: 92%
“…or greater-and less than 10% requiring surgical intervention. 7,8,19 In the US, pediatric TBI is responsible for 435,000 emergency department visits; 37,000 hospitalizations; and 2685 deaths per year. 26 Few studies have characterized the epidemiology of pediatric TBI in African countries.…”
mentioning
confidence: 99%
“…Šis santykis, įvairių šalių duomenimis, įvairuoja nuo 1,52 : 1 Australijoje, JAV [2,5,12] iki 2,8 : 1 Korėjoje, Didžiojoje Britanijoje, Taivane [3,9,12]. Be to, sutariama ir dėl to, kad iki 1 metų amžiaus šis santykis panašus, o su amžiumi nukentėjusių berniukų skaičius didėja [2,3,5,9,10]. Šiuo požiūriu mūsų atliktų tyrimų duomenys sutampa.…”
Section: Rezultatų Aptarimasunclassified